Impact of Metabolic Surgery in Cancer Prevention / Impacto da Cirurgia Metabólica na Prevenção de Cancro - Francisca José Lopes Barbosa (2020)
Background: Obesity and its related complications represent a huge burden is today's medical practice and have a great impact in the mean life expectancy. Obese individuals have an increased risk of cancer and the mechanisms linked to this risk have been study for years so that a physiopathology base can be established. Metabolic surgery is a recent concept that integrates the systemic alterations that happen after surgery induced weight loss and that can possibly revert the increased cancer risk associated with obesity. This paper reviews the main mechanisms linked with the increased cancer risks in these individuals and how metabolic surgery can help preventing them. Methods: This study is narrative review based on PubMed/MEDLINE literature search. In a first-stage search, 1312 results were obtained and after careful reading and selection, a total number of 64 articles were included in this review, including also a references research. Results: Metabolic surgery is associated with a decrease in the overall cancer risk, all-cause mortality and cancer-related mortality in obese individuals. Apart from the great amount of weight loss, there is also a reduction in the low-grade chronic inflammation, in circulating levels of estrogen, insulin and consequent insulin-like growth factor-1, all of which have been proved to have mitogenic proprieties. Conclusion: This type of surgery is associated with an undoubtable risk reduction of hormone-related cancers such as endometrium and breast cancers and also linked with a decrease number in pancreatic and liver cancers cases. The relation between surgery and gastrointestinal cancers is not so fully understood and the results are not unanimous. The anatomical gastrointestinal alterations may be implicated in some cases of colorectal cancer after surgery.